195k views
0 votes
(-5+ i)(12- i)(-3).

User Raykud
by
4.6k points

2 Answers

3 votes

Answer:

177 - 51i

Explanation:


(-5+ i)(12- i)(-3).


(-5+ i)(12- i)

Apply the distributive property


-5X12-5(-i)+
(-i)X12+(i)
(-i)

Simplify


-60+5i+12i-1i^(2)

Reduce the imaginary units using the property
i^(2) =-1


-60+5i+12i-1(-1)

Simplify and write in the standard form of
a+bi


-59+17i\\(-59+17i)(-3)\\177-51i

Hope it helps u:)

User Ramarao Amara
by
5.1k points
7 votes

Answer:


177 - 51i

Explanation:

Given expression:


(-5+i)(12-i)(-3)

Use the FOIL method to multiply the first two parentheses:


\implies \left(-5 \cdot 12 -5 \cdot -i +i \cdot 12 + i \cdot -i\right)(-3)


\implies \left(-60 +5i +12i -i^2\right)(-3)


\implies \left(-60 +17i -i^2\right)(-3)

Multiply:


\implies -60 \cdot -3 +17i \cdot -3 -i^2 \cdot -3


\implies 180-51i+3i^2

Apply the imaginary number rule: i² = -1


\implies 180-51i+3(-1)

Simplify:


\implies 180-51i-3


\implies 177-51i

User Malfist
by
4.2k points